Relationship of Parenting with Child Interpersonal Intelligence in Wonokerto Village, Lumajang Regency - Yessy Nur Endah Sary (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Parenting is a pattern of interaction between parents and children or can be said to be the attitude or behavior of parents when interacting with children, including how to apply the rules, teach values or norms, give attention and love and show good attitudes and behaviors so that they become role models for their children. The purpose of this study was to analyze the relationship of parenting parents with children interpersonal Intelligence in Wonokerto, Lumajang. The research design used Correlational analytical. The Samples are 44 kindergarten students with using total sampling. The data analysis with Spearman Rank. The results of the relationship analysis of parenting parents with kindergarten interpersonal intelligence obtained that the practice of the majority parenting is authoritarian parenting as much as 20 (45.5%). Interpersonal intelligence of kindergarten children is a good majority of 40 (90.9%). The conclusion of this study is that there is a relationship between parenting pattern with children interpersonal Intelligence in Wonokerto, Lumajang.